Bailey's Industrial Oil and Fat Products 2020
DOI: 10.1002/047167849x.bio120
|View full text |Cite
|
Sign up to set email alerts
|

Lipids in the Treatment of Mental Disorders

Abstract: The management of mental disorders is dominated today by pharmacotherapy, while nutrition and dietary approaches play a minor role. Evidence from both preclinical and clinical investigations suggests an important role for lipids in major mental disorders. Alterations in the concentration, organization, and metabolism of lipids are associated with mood disorders, schizophrenia, and behavioral problems in childhood. The lipid composition of the brain can be influenced by nutrition, environmental factors, and beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 232 publications
0
4
0
Order By: Relevance
“…In particular, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) have been linked to the maintenance of mental health. Dietary deficiencies of these fatty acids have been implicated in the pathophysiology and increased risk of a range of mental disorders, including unipolar depression, bipolar disorder, schizophrenia, dementia, autism and attention-deficit/hyperactivity disorder (Lange, 2020a(Lange, , 2020b. The findings of animal experiments suggest that omega-3 fatty acids may affect several of the neurobiological mediators believed to be involved in the pathophysiology of major depressive disorder (Müller et al, 2015).…”
Section: Rationale For the Use Of Omega-3 Fatty Acids In Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) have been linked to the maintenance of mental health. Dietary deficiencies of these fatty acids have been implicated in the pathophysiology and increased risk of a range of mental disorders, including unipolar depression, bipolar disorder, schizophrenia, dementia, autism and attention-deficit/hyperactivity disorder (Lange, 2020a(Lange, , 2020b. The findings of animal experiments suggest that omega-3 fatty acids may affect several of the neurobiological mediators believed to be involved in the pathophysiology of major depressive disorder (Müller et al, 2015).…”
Section: Rationale For the Use Of Omega-3 Fatty Acids In Depressionmentioning
confidence: 99%
“…The need for the development of further medications for the treatment of depression has repeatedly been emphasized (Insel, 2015;Miller, 2010), as has the need for novel approaches to the prevention and therapy of depression. Nutrition and diet quality have been shown not only to play an important role in the promotion of metabolic health (Bennett et al, 2015), but also to be involved in mental health and to be factors able to modify mental disorders (Lange, 2018(Lange, , 2020a(Lange, , 2020bMarx et al, 2017). For example, the risk of depression has been reported to be inversely associated with the Mediterranean diet, which comprises limited quantities of processed foods and large amounts of vegetables, fruit, nuts, seeds, wholegrains and fish (Lai et al, 2014;Opie et al, 2015;Psaltopoulou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several dietary interventions, including gluten-free and casein-free diets (Lange et al, 2015;Reissmann et al, 2020) and omega-3 fatty acid supplementation (Lange, 2020a), have been suggested as complementary and alternative medicine treatments in ASD. However, in view of the less than convincing evidence in support of these dietary approaches, it would be premature to recommend them as alternatives in the management of ASD (Lange, 2020d;Reissmann et al, 2020).…”
Section: Gut Microbiota In Mental Disordersmentioning
confidence: 99%
“…The need for the development of further medications and novel approaches to the prevention and treatment of depression has therefore been emphasized (Insel, 2015;Miller, 2010). Diet and nutrition have been found not only to be critically involved in the promotion of metabolic health (Bennett et al, 2015), but also to play a role in mental health and to be capable of modifying mental disorders (Lange, 2018;Lange, 2020a;Marx et al, 2017). The risk of depression appears to be inversely associated with the Mediterranean diet (Lai et al, 2014;Opie et al, 2015;Psaltopoulou et al, 2013), while Western diets have been reported to be positively correlated with depression (Lai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%